Dendrimeric amide- and carbamate-linked lysine-based efficient molecular transporters - Yadav, Amit Kumar; Dey, Namit; Chattopadhyay, Sabyasachi; Ganguli, Munia; Fernandes, Moneesha (Organic & Biomolecular Chemistry, 2017)
Amide- and carbamate-linked dendrimeric oligomers are reported as molecular transporters. They effectively complex with pDNA and transport it into cells at an efficiency superior to Lipofectamine, when complexation is carried out by incubation overnight. The carbamate-linked K2C is superior to amide-linked K2A; their pDNA complexes have very low associated cytotoxicity.